ANALISIS HUKUM TERHADAP KETENTUAN SYARAT BERBANKIR TUNGGAL DALAM PENYEDIAAN KREDIT KEPADA DEBITUR (STUDI PADA PT. BANK MANDIRI, TBK CABANG MEDAN) - DEWI ARIANTI NESTIANTA PURBA (PREMISE LAW JURNAL, 2016)
The result of the research showed that the position of the Bank and the clients in a credit contract is never in balance. The reason of PT Bank Mandiri for applying the requirement for Single Banker in giving credit to debtors is merely to apply prudential principle. The legal consequence of its implementation of applying the requirement for Single Banker in credit contract of PT Bank Mandiri, Tbk related to the Law on Hypothecation is that it will be legally null and void because it is contrary to Law No. 4/1996 on Hypothecation. In practice, however, a credit contract is never legally null and void because of applying the requirement for Single Banker since it is generally practiced by the banks in Indonesia. It is recommended that Bank Indonesia as the establisher and supervisor of the National Banking standardize the content of credit contract of each bank operating in Indonesia by paying attention to the balance in right between a debtor and a bank. In order to make it balanced and righteous in the obligation of creditor and debtor, before signing the credit contract, both parties should understand its content so that the right and obligation of clients can be completely understood. Keywords: Credit Contract, Requirement for Single Banker